Young Adults’ Attitudes to Contraception Mediate their Likelihood of Use - Cramer, Kenneth M.; DeRoy, Emma (American Journal of Social Sciences and Humanities, 2019)
Whereas 91% of unwed mothers are under 21 years, researchers and health policy advisers hope to unpack the association between a woman’s wish to avoid becoming pregnant and the intention to use birth control, a relation we hypothesized to be mediated by various attitudes to contraceptive use (including cost, ease of use, extra planning, even morality). In total, 22 potential mediators were evaluated using the Relationship Dynamics and Social Life Study – consisting of 1003 Michigan women aged 18-20 years from Caucasian, African, and Hispanic American backgrounds. Results showed a significant relation between avoiding pregnancy and contraceptive use; when divided by ethnic background, the negative association was higher for African Americans compared to Caucasians, and higher still for Hispanics. This relation was mediated by each of: premarital sex is OK if attracted; faster recovery following pregnancy if young; birth control involves too much planning; it’s a hassle to use birth control; and marital relations improve with the advent of children. When divided by ethnicity, we unexpectedly uncovered several suppressor variables, following whose extraction improved the original association. Implications for researchers and health professionals, as well as directions for future research, are outlined.